Activity and concentration of non-proteolyzed phosphoenolpyruvate carboxykinase in the endosperm of germinating castor oil seeds: effects of anoxia on its activity - Martín, Mariana; Plaxton, William C.; Podestá, Florencio E. (Physiologia plantarum, 2007)
Phosphoenolpyruvate carboxykinase (PEPCK; EC 4.1.1.49) catalyses the reversible decarboxylation of oxaloacetate to phosphoenolpyruvate in the gluconeogenic production of sugars from storage lipids in germinating oil seeds. The enzyme is quite susceptible to limited proteolysis during extraction. Immunoblotting was used to diagnose unwanted in vitro proteolytic activity against PEPCK from germinating castor oil seeds (COS) by following the disappearance of its native 74‐kDa subunit and concomitant appearance of a truncated 64‐kDa polypeptide. Alkaline pH and the inclusion of thiol protease inhibitors effectively prevented COS PEPCK proteolysis during incubation of clarified COS extracts at 4°C. The carboxylating and decarboxylating activities and concentration of non‐proteolyzed COS PEPCK were investigated during germination. This is the first report in which both activities catalyzed by PEPCK were measured in vitro during a whole developmental process. Carboxylating activity and the level of immunoreactive 74‐kDa PEPCK polypeptides rapidly increased in parallel to maximal values by day 5 and then significantly declined over the subsequent 2 days. In contrast, decarboxylating PEPCK activity was much higher over the 7 days of growth examined. In addition, the effect on PEPCK activity while changing the endosperm from aerobic (when gluconeogenesis predominates in the tissue) to anaerobic conditions (where the tissue becomes glycolytic) was studied. While PEPCK decarboxylating activity remained almost constant, carboxylating activity declined to undetectable levels in response to anaerobiosis. These and the developmental profile results suggest that COS PEPCK may be subject to a mechanism of post‐translation control that selectively inhibits the carboxylating, but not the decarboxylating activity.